Trauma Theory and Theological Engagement: An Appraisal on Trends in Trauma Hermeneutics - Musa, Hassan (Scriptura, 2025)
Studies on trauma theory and its significance to biblical hermeneutics are largely unknown in Africa, especially in the West African context. But due to recent sad events of conflicts and violence, trauma is now being explored for possible engagement in biblical and practical theological scholarship. This essay is an appraisal on the crucial problem of trauma studies in an African context, from theological and pastoral perspectives. Certain issues have been highlighted as the background that leads to trauma studies in the history of the modern world and even in modern African contexts. The contribution that this essay provides is mainly in terms of introducing its readers to the possible meaning(s) of trauma, the various trends and types of trauma, as well as some of the useful materials and theological perspectives on engaging trauma theory. Thus if this study further generates more concern and interest in engaging the African human condition of trauma from more rigorous/critical theological, psychological and pastoral perspectives, with the possible aim of overcoming it, toward a state of good healing and the restoration of human dignity, then the aim of this essay will have been achieved.